CoviHealth: Novel approach of a mobile application for nutrition and physical activity management for teenagers - Vanessa Villasana, María; Miguel Pires, Ivan; Sá, Juliana; M Garcia, Nuno; Pombo, Nuno; Zdravevski, Eftim; CHorbev, Ivan (My University, 2019)
The increasing number of teenagers with obesity and sedentary lifestyle is related to the poor habits of diet and physical activity. There is a large diversity of mobile applications related to diet control and physical activity, mainly directed to adults and without any medical control. CoviHealth project consists of the implementation of a mobile application for young people to promote healthy dietary habits and physical activity based on anthropometric parameters control and gamification. The main contribution of this paper is a detailed specification of an integrated mobile for promoting healthy habits for young people. Additionally, it leverages the effects of the gamification and medical control on stimulating education with healthy habits. Even though other mobile applications have some features that the proposed application has, to the best of our knowledge, a standardized specification for the integration of activity recognition, healthy habits and food intake for teenagers lacks.
Keywords: Nutrition, Physical activity, Mobile applications, Teenagers, Health